SRM sensorless for position control based on a frequency modulation system - Rafael, Silviano (2021)
This paper presents a study of a system to detect the angular position of the shaft of an 8/6 Switched Reluctance Machine (SRM) for position control. The detection system is independent of the machine circuits and is based on the indirect measurement of the induction coefficient, using a diagnostic coil. This induction coefficient, variable with the angular position, is the variable element of an oscillator, producing a frequency modulation. The intrinsic problems that this indirect position measurement system presents, particularly related with position control, are explained. The influence of the machine temperature, of the rotor speed and of the magnetic circuit saturation are also discussed.